2013
DOI: 10.1021/ml400316p
|View full text |Cite
|
Sign up to set email alerts
|

Preparative Microfluidic Electrosynthesis of Drug Metabolites

Abstract: In vivo, a drug molecule undergoes its first chemical transformation within the liver via CYP450-catalyzed oxidation. The chemical outcome of the first pass hepatic oxidation is key information to any drug development process. Electrochemistry can be used to simulate CYP450 oxidation, yet it is often confined to the analytical scale, hampering product isolation and full characterization. In an effort to replicate hepatic oxidations, while retaining high throughput at the preparative scale, microfluidic technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 29 publications
1
69
0
8
Order By: Relevance
“…It is mostly used to prepare hydroxylated metabolites in the benzylic position or in aromatic rings, provided that it is activated by electron donating groups, such as phenols, ethers, or anilines (Jurva et al, 2003). Despite the high number of investigated compounds, very few studies have prepared sufficient amounts for NMR analysis (Stalder and Roth, 2013;Fredenhagen et al, 2014). In our hands, electrochemistry is especially useful for compounds that are sparingly water soluble and that therefore are not reactive in aqueous enzyme reactions (Schroer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is mostly used to prepare hydroxylated metabolites in the benzylic position or in aromatic rings, provided that it is activated by electron donating groups, such as phenols, ethers, or anilines (Jurva et al, 2003). Despite the high number of investigated compounds, very few studies have prepared sufficient amounts for NMR analysis (Stalder and Roth, 2013;Fredenhagen et al, 2014). In our hands, electrochemistry is especially useful for compounds that are sparingly water soluble and that therefore are not reactive in aqueous enzyme reactions (Schroer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A microflow electrolysis cell with a similar design has recently been employed for the oxidation of substituted toluenes [4] and for the investigation of the metabolites from the oxidation of a number of drugs [5] although it is clear from the performance reported that the cell was operated away from the optimum conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione conjugates could be synthesized in a subsequent flow reactor, connected directly to the output of the electrochemical flow cell. 60 Pd-BrettPhos 30% C 7 H 15 CON(CH 3 ) 2 2-MeTHF …”
Section: Reactor Type Mattersmentioning
confidence: 99%